Pengaruh Kepercayaan Diri dan Kemandirian Belajar Terhadap Hasil Belajar Kimia Peserta Didik Kelas XI SMAN 1 Kerinci Kanan - Ayu Wulandari; Erviyenni Erviyenni; Abdullah Abdullah (Chemistry Education Practice, 2025)
This study aims to determine the effect of self-confidence and learning independence on chemistry learning outcomes of class XI students of SMAN 1 Kerinci Kanan. The method used is a correlational quantitative approach. This study uses a correlational quantitative approach with a sample size of 99 students. data collection techniques through questionnaires, value documentation, and interviews. The results of descriptive statistical analysis show that the average self-confidence and learning independence of students are in the moderate to high category and self-confidence has a positive and significant effect on learning outcomes with a significance value of 0.045 and a correlation of 0.890. Learning independence also has a significant effect with a significance value of 0.042 and a correlation of 0.567. Simultaneously, self-confidence and learning independence have an influence of 65.2% on learning outcomes, while the rest is influenced by other factors. The conclusion of this study is that self-confidence and learning independence play an important role in improving chemistry learning outcomes, so both need to be developed in the learning process.